Morse Code Translator Applications Based on Computer Using Radio Transmission - Heru Ismanto (International Conference on Engineering and Technology Development (ICETD), 2012)
Development of information technology today is growing very rapidly. It can be seen from the increasing sophistication of technology used to process and get information. However, not all information may be known by the general public, because there is confidential information. So that confidential information can omly be know and understood by a particular party.The method used to secure confidential information may include an encryption technique. With this technique ancoded information into an information can not be read or is known by parties who are not interested. One form of morse code is a password that can be used to send confidential information.Along with this there was made an application that serves to translate the code-Morse code, so users no longer need to send and interpret the code-the conventional morse code. To make the application required the application software that supports and is compatible with applications that will be made and also needed a trainer for testing radio Morse code input. If the application can pass the test with good result, it can be used as an application of Morse code translator.